ANALYSIS OF POWER LOSSES CALCULATION IN MEDIUM VOLTAGE NETWORK OF FEEDER SERIMPI, PAM 1 AND PAM 2 AT NETWORK AREA GAMBIR PT.PLN (PERSERO) DISTRIBUSION JAKARTA RAYA AND TANGERANG - Liem Ek Bien, Liem Ek Bien; Kasim, Ishak; Pratiwi, Erni Aprianti (Jurnal Teknik Elektro, 2009)
Power losses at medium voltage network distribution systems cannot be avoided. Although its value is difficult to know exactly but it can be calculate. The value is influenced by load and line resistance, it is one of the aspects of efficiency on power electric distribution. This paper uses two calculation methods. The first method is basic formula which PLN usually use based on field data acquisitioned. The second method is calculation based on research estimation power losses per year; this method is providing (IEEE, 2006: 1092). Keywords: Medium Voltage Network, Distribution Feeder, Llosses.